1993
DOI: 10.1128/jcm.31.8.1971-1974.1993
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole susceptibility testing for Helicobacter pylori: comparison of disk, broth, and agar dilution methods and their clinical relevance

Abstract: Since the methods for metronidazole susceptibility testing of Helicobacter pylori have not been standardized or validated, we compared three methods that are used to test the metronidazole susceptibilities of 25 isolates of H. pyloni. Specifically, we examined the methods of Steer's replicator agar dilution, tube broth microdilu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 14 publications
3
46
0
Order By: Relevance
“…Several studies have reported that when a patient is infected by a metronidazole-resistant strain, the possibility of obtaining eradication with treatment including metronidazole is lower than in patients infected with metronidazole-susceptible strains [15,26]. A 70 and 30% eradication rate has been found by Moayadi et al [27], 100 and 53% by Ching et al [21], 81 and 16% by DeCross [28] on susceptible and resistant H. pylori-infected patients. Other authors found 100 versus 82% in susceptible or resistant strains-infected patients [29] or eradication in eight out of nine versus 63 of 67 in metronidazole-resistant or -susceptible-infected patients [6], when triple therapy including metronidazole and clarithromycin was used.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that when a patient is infected by a metronidazole-resistant strain, the possibility of obtaining eradication with treatment including metronidazole is lower than in patients infected with metronidazole-susceptible strains [15,26]. A 70 and 30% eradication rate has been found by Moayadi et al [27], 100 and 53% by Ching et al [21], 81 and 16% by DeCross [28] on susceptible and resistant H. pylori-infected patients. Other authors found 100 versus 82% in susceptible or resistant strains-infected patients [29] or eradication in eight out of nine versus 63 of 67 in metronidazole-resistant or -susceptible-infected patients [6], when triple therapy including metronidazole and clarithromycin was used.…”
Section: Discussionmentioning
confidence: 99%
“…Suspensions of fresh cultures were made in saline and turbidity adjusted to 9 × 10 8 or 1.5 × 10 8 bacteria/ml (corresponding to McFarland standards 3 and 0.5, respectively). H. pylori is a fastidious organism and it has been reported that using a McFarland standard of 3 or 4 actually yields counts of only 5 × 10 6 cells/ml [15]. The higher inoculum was used for antibiograms with antibiotic disks and both inocula were used to determine the antimicrobial activity of the plant extracts.…”
Section: Anti-h Pylori Susceptibility Testsmentioning
confidence: 99%
“…We believe that this is a genuine phenomenon, as our antibiotic sensitivity testing was confirmed by both the disk diffusion and the agar dilution methods. Both tests were validated as reliable ways of checking antibiotic sensitivity in previous studies [23,24]. The mechanism for the development of resistance to metronidazole is not known.…”
Section: Dna Fingerprinting and Ribotypingmentioning
confidence: 99%